Assessment of Knowledge about First Aid Methods, Diagnosis, and Management of Snakebite among Nursing Students: A Cross-Sectional Study from Palestine - Isra K. Kharusha; Suha S. Sulaiman; Ahmad M. Samara; Samah W. Al-Jabi; Sa’ed H. Zyoud (Emergency Medicine International)
Background. Snakebite is a serious and important medical emergency encountered in many parts of the world. The estimated number of victims of venomous snakebites in Palestine is about 100 to 150 annually, with death occurring in 2 to 3 of them. This study was designed to assess the level of knowledge on the diagnosis and management of snakebites among nursing students in Palestine, as well as their attitude towards snakebites. Methods. This was a cross-sectional survey that took place at An-Najah National University. Two hundred nursing students were asked to fill a questionnaire that was developed to assess the participants' knowledge and attitude regarding snakebite's diagnosis and management. Different knowledge scores were calculated, and the relationships between students' knowledge and their characteristics were calculated by implementing the Mann–Whitney U test and the Kruskal–Wallis test. The statistical significance limit of p values was set at 0.05. Results. The majority of the participants (57%) were fourth-year students with an average age of 20.7 ± 1. Areas of knowledge and the participants’ mean scores on them were as follows: Vipera palaestinae snake, 5.1/13; signs and symptoms, 9.6/16; laboratory investigations, 6.1/10; anti-venom, 4.2/11; and first aid, 6.6/15. The only statistically significant differences in knowledge were between male and female students on Vipera palaestinae (male students scored higher, p value = 0.004) and between different types of residence (village dwellers scored the highest, p value = 0.041). Conclusions. We found knowledge gaps in many aspects of snakebite’s diagnosis and management among nursing students in Palestine. Based on the results of this study, we suggest integrating more materials on this topic in the curriculum of Palestinian nursing schools, as well as more practical training, which will positively reflect on the care for snakebite victims.